Analysis of e-customer relationship management BPJS in maintaining customer loyalty - Rahmani, Vania Taufik; Utami, Nadia Wasta; Darmawan, Ibnu (Jurnal Komunikasi, 2025)
This research aims to investigate the e-CRM strategies employed by BPJS to sustain customer loyalty. A qualitative descriptive method is utilized in this study. Data gathered through interviews and observations conducted at the BPJS. The research framework is informed by Francis Buttle's Customer Relationship Management theory, which has been adapted to the context of electronic technology in CRM implementation. The findings indicate that BPJS's e-CRM strategy can be categorized into three levels: strategic, operational, and analytical. At the strategic level, BPJS implements a high-level cultural calendar and provides digital service channels that enhance convenience, speed, and reliability in service delivery. At the operational level, BPJS automates various marketing, sales, and service processes. Finally, at the analytical level, BPJS conducts customer journey mapping, which encompasses the components of I-Cari, I-Belajar, and I-Daftar.